Characterization of bio-oils from jatropha residues and mixtures of model compounds - Prapaporn Prasertpong (2018)
This study analyzed the composition of actual bio-oils produced by fast pyrolysis of jatropha and compared these with model bio-oils prepared based on typical biomass as reported in the literature. Bio-oils were found to consist primarily of organic acids, phenols, ketones, and alcohols, which were modeled using acetic acid, phenol, acetone, and ethanol, respectively. Properties of both the real and model bio-oils were subsequently characterized. While the phy sico-chemical characteristics of these bio-oils varied widely, long chain acids, such as oleic and palmitic acids, accounted for over 70%. Real bio-oils had higher energy content, density, viscosity, acidity, and flash and pour points than the model oils, because of the variety of large and heavy molecules present in the real bio-oils compared to the light compounds that were used to represent the model oils.